The Development and Usability of a Mobile App for Parents of Children with ADHD - Costina-Ruxandra Păsărelu; Reka Kertesz; Anca Dobrean (MDPI AG, 2023)
Background: Attention-Deficit/ Hyperactivity Disorder (ADHD) is one of the most prevalent mental health problems in children. Behavioral parent training (BPT) is the first-line treatment recommended by clinical guidelines; however, parental dropout is high. Mobile apps could be used as an adjunct to BPT in order to increase treatment adherence, homework compliance, and parental engagement. In this paper, we describe the development process of a mobile app for parents of children with ADHD. Methods: We conducted a study to investigate parents' perceived usability of the ADHD Coping Card. Results: The mobile app developed has a high usability. Future improvements in the app were suggested by parents. Conclusions: Given the increasing importance of digital mental health interventions in psychotherapy, it is important that future research is conducted with a higher number of participants to investigate the key factors implicated in choosing such an intervention in the future, both by parents and by mental health specialists. A mobile app can be used as an add-on in psychotherapy with parents of children with ADHD. Digital health interventions could help surpass gaps in treatment access for child mental health problems.